Sharia Governance in the Digital Financial Ecosystem: OJK Regulation and DSNMUI Fatwa: Sharia Governance - Yuliana Siti Sholaika; Amin Wahyudi; Miftah Pahlevi (AL-IKTISAB: Journal of Islamic Economic Law, 2025)
This research discusses sharia governance in the digital financial ecosystem, which is experiencing rapid development in line with the transformation of technology-based financial services. Digital financial services are currently facing new challenges in terms of sharia governance, particularly between OJK regulation and DSN-MUI fatwa. DSN-MUI Fatwa No. 117/2018 emphasizes that digital platforms function as representatives (wakalah), while POJK No. 10/2022 provides space for platforms to act as digital business operators with authority over system management, algorithms, and fee setting. This difference in construction has the potential to give rise to dual functions of platforms that lead to digital hilah practices that can weaken sharia principles. This research aims to analyze the gap between OJK regulation and DSN-MUI fatwa in the application of sharia governance in the digital finance ecosystem and to formulate a model for strengthening sharia governance that is adaptive to technological developments. This research method uses library research on legislation, OJK regulation, DSN-MUI fatwa, and relevant scientific articles. The results of the research show that there are three main gaps, namely in the aspects of the position and authority of digital platforms, algorithmic transparency in determining fees and financing, and mechanisms for monitoring sharia compliance in the digital world. This research provides solutions in the form of harmonizing regulations between OJK regulation and the DSN-MUI fatwa to strengthen the role of DPS based on algorithmic audits and to develop a digital sharia governance framework as a standard for sharia governance in the digital finance sector that is more comprehensive and responsive to technological developments. The findings of this research are expected to have important implications for regulators, industry, and sharia supervisors in building a digital financial ecosystem that is not only innovative but also trustworthy, fair, and oriented towards public interest.